REFLECTING ON THE ROLE OF PHYSICAL EDUCATION: BETWEEN NECESSITY, WELLNESS AND RECREATION - Maria LULESCU (Challenges of the Knowledge Society)
Physical education has known during its long contribution to the human history both a continuation of old thinking such as mens sana in corpore sano, as well as new ideas, meant to support the role of children and adults in a changing environment. Major contributions about its role nowadays have discussed the relation with human metabolism and fitness (Drăgan 1978; Cheța and Mihalache 1989) while recent contributors explore its role in multi-cultural educational environments (Bronikowski in Hardman and Green 2011, Howie și Pate 2012). At present, schools and universities have adapted their curricula to turn physical education in a tool able to do more than simply stimulating the body and the mind work together: from a reduction of sedentary activities and focus on depending on computer to an active component of everyday lifestyle. The purpose of this paper is to explore current trends in the approach of higher education institutions, students and teachers to combine physical education as a summum of activities leading to wellness and recreation for the all actors involved.